Pemanfaatan Lahan Di Bawah Tegakan Pepaya dalam Budidaya Sawi Pakcoy: Land Utilization Under Papaya Stands in The Cultivation of Mustard Greens Pakcoy - Rahmadani, Fitri; Nofrianil, Nofrianil; Ibnusina, Fedri (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
This research was conducted to utilize the land under the stand as a strategy to increase agricultural area in vegetable cultivation.This study used a Group Randomized Design (GRD) with 3 levels of treatment, namely land without shade, land under immature papaya stands and land under mature papaya stands with 9 replications simultaneously. The total population used was 648 populations with 12 samples of each replication determined by simple random sampling, so the total number of samples was 324. Data analysis was processed using Analysis of Variance (ANOVA) followed by Duncan Multiple Range 5%. (DMRT) test was tested using SPSS 26 software. The results showed that the utilization of land under papaya stands in the pakcoy mustard production business gave the results no significant effect on the observation of variable number of leaves, stem diameter, root crown ratio, and fresh weight of plants. The treatment of shade and no shade has no significant effect on pakcoy. So that in the future it can be applied to the cultivation of pakcoy.